Rasionalisasi pendidikan Islam di Era disrupsi: Analisis stratifikasi status sosial dan ketimpangan akses dalam perspektif Max weber - Musyafa, Muhammad Zakki; Khasanah , Nur (Jurnal Pendidikan Agama Islam, 2025)
Acceleration of technology has fundamentally reshaped the social fabric, ushering in the Disruption Era marked by the pervasive hegemony of instrumental rationality (Zweckrationalität) across institutional domains. This study aims to analyze how the subsequent shift in the social function of Islamic Education, amidst intense demands for digital efficiency, impacts social status stratification and access inequality. Utilizing a comparative literature review framed by Max Weber's Rationalization Theory (via Talcott Parsons' interpretation), the research finds that the function of Islamic Education shifts drastically from substantive value transmission to functional competence. This change, driven by digital bureaucratization and market commercialization, triggers De-Magification (disenchantment) and structurally creates a digital 'Iron Cage'. The study concludes that Islamic Education risks becoming an agent of class stratification rather than social integration, demanding a vital balance between insstrumental rationality and value rationality to ensure equitable access and ethical sustainability